2017
DOI: 10.1175/wcas-d-16-0120.1
|View full text |Cite
|
Sign up to set email alerts
|

WMO Assessment of Weather and Climate Mortality Extremes: Lightning, Tropical Cyclones, Tornadoes, and Hail

Abstract: A World Meteorological Organization (WMO) Commission for Climatology international panel was convened to examine and assess the available evidence associated with five weather-related mortality extremes: 1) lightning (indirect), 2) lightning (direct), 3) tropical cyclones, 4) tornadoes, and 5) hail. After recommending for acceptance of only events after 1873 (the formation of the predecessor of the WMO), the committee evaluated and accepted the following mortality extremes: 1) “highest mortality (indirect stri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 16 publications
0
23
0
Order By: Relevance
“…Accompanied by high winds, heavy rainfall, and storm surges, tropical cyclones (TCs) are one of the most devastating types of natural disasters to coastal regions and can inflict huge economic and societal losses (Lee and Wong, 2007;Needham et al, 2015;Cerveny et al, 2017;Khouakhi et al, 2017). The past five decades have seen detectable anthropogenic warming of the climate system, and many modeling studies have suggested that the anthropogenic warming could exert remarkable influences on TCs (Knutson et al, 2010;Murakami et al, 2012a;Patricola and Wehner, 2018;Knutson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Accompanied by high winds, heavy rainfall, and storm surges, tropical cyclones (TCs) are one of the most devastating types of natural disasters to coastal regions and can inflict huge economic and societal losses (Lee and Wong, 2007;Needham et al, 2015;Cerveny et al, 2017;Khouakhi et al, 2017). The past five decades have seen detectable anthropogenic warming of the climate system, and many modeling studies have suggested that the anthropogenic warming could exert remarkable influences on TCs (Knutson et al, 2010;Murakami et al, 2012a;Patricola and Wehner, 2018;Knutson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Lightning is responsible for human injuries and fatalities, the death of livestock, and house and forest fires. [1][2][3] It is also a major source of electromagnetic interference and damage to electronic circuits, buildings, and other exposed man-made structures such as transmission lines, wind turbines and photovoltaics. Based on the reports for 1023 fatalities associated with natural hazard processes in Switzerland during the period from 1946 to 2015, more than 16% of the cases were caused by lightning, making it the second most frequent cause of loss of life among the natural hazards in Switzerland.…”
Section: Introductionmentioning
confidence: 99%
“…The combined effect of more extreme precipitation scenarios (including drought) and higher temperatures is a projected increase in fire weather [3], with events such as the 2016 Fort McMurray, Alberta Wildfire being attributed with reasonable confidence to anthropogenic climate change [9,10]. The World Meteorological Organisation has reported an increase in the number and cost of extreme events world-wide [11], which is supported by the Insurance Bureau of Canada and a recent report by the Intact Centre on Climate Adaption [12]. The Canadian Natural Disaster Database (CDD) provides information on significant disaster events tracked by the Emergency Management Framework meeting a specific set of criteria, documenting when and where the event occurred, number of injuries, evacuations and fatalities, and the cost [13].…”
Section: Hydro-climatic Extremesmentioning
confidence: 99%